2022
DOI: 10.1097/meg.0000000000002424
|View full text |Cite
|
Sign up to set email alerts
|

Liver cirrhosis prediction for patients with Wilson disease based on machine learning: a case–control study from southwest China

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives License 4.0 (CCBY-NC-ND), where it is permissible to download and share the work provided it is properly cited. The work cannot be changed in any way or used commercially without permission from the journal.Objectives Wilson disease (WD) is a rare autosomal recessive disease caused by an ATP7B gene mutation. Liver cirrhosis is an important issue that affects the clinical management and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
2
4
1
Order By: Relevance
“…In addition, we found that there was a weak negative correlation between ATT and SWM, indicating that the level of SWM did not increase when ATT was at a high level, which was consistent with the fact that liver steatosis in patients with WD occurred before liver brosis, and it was no longer the main pathological change in the stages of liver brosis and cirrhosis, making SWM a noninvasive index for the assessment of liver brosis in patients with WD [23]. However, it remains to be clari ed whether SWM can be used as a sensitive index for the assessment of early hepatic steatosis.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, we found that there was a weak negative correlation between ATT and SWM, indicating that the level of SWM did not increase when ATT was at a high level, which was consistent with the fact that liver steatosis in patients with WD occurred before liver brosis, and it was no longer the main pathological change in the stages of liver brosis and cirrhosis, making SWM a noninvasive index for the assessment of liver brosis in patients with WD [23]. However, it remains to be clari ed whether SWM can be used as a sensitive index for the assessment of early hepatic steatosis.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, we found that there was a weak negative correlation between ATT and SWM, indicating that the level of SWM did not increase when ATT was at a high level, which was consistent with the fact that liver steatosis in patients with WD occurred before liver fibrosis, and it was no longer the main pathological change in the stages of liver fibrosis and cirrhosis, making SWM a noninvasive index for the assessment of liver fibrosis in patients with WD [24]. However, it remains to be clarified whether SWM can be used as a sensitive index for the assessment of early hepatic steatosis.…”
Section: Discussionsupporting
confidence: 82%
“…Chen et al used EmpowerStats software to predict patients with WD cirrhosis, including blood routine, 24-h urine copper, and serum ceruloplasmin in 346 patients with WD. It was discovered that the top five important predictors were platelet large cell count (P-LCC), red cell distribution width CV (RDW-CV, CV means corpuscular volume), serum ceruloplasmin, age at diagnosis, and mean corpuscular volume (MCV) ( 22 ).…”
Section: Discussionmentioning
confidence: 99%